Indonesia’s Role in the Rise of East Asia amid China's Ascendancy - Pramono, Sugiarto; Raharjo, Wahyu Arif (Nation State: Journal of International Studies, 2023)
China is leading East Asia as the epicentrum of growth in the third decade of 21st century, however, the role of Indonesia is eminent in this rise. Meanwhile, the struggle over influence in the region is acrimonious, as USA, China and Russia are vying for support from countries in this strategic region. Through the lens of neorealism, this study attempts at examining the role of Indonesia in rising East Asia. It argues that Indonesia plays major role especially in mediating and balancing both US – China rivalries through carefully crafted diplomatic strategies. Indonesia provides regional frameworks within which cooperations between opposing countries is possible, while at the same time safeguarding these cooperations through balancing act. Indonesia's strategic position enables it to serve as a global balancer by accepting agreements with China and maintaining close security ties with the United States. Through prudent policies, Indonesia upholds regional stability and plays an effective mediating role among major global powers.